1992
DOI: 10.1007/bf01406376
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral salt wasting syndrome distinct from the syndrome of inappropriate secretion of antidiuretic hormone (SIADH)

Abstract: Two cases with pituitary tumour developed postoperative hyponatraemia which was not caused by inappropriate secretion of antidiuretic hormone. The one case with non-functioning macro-adenoma showed severe hyponatraemia (116 mEq/l) on day 11 after trans-sphenoidal surgery in association with diabetes insipidus (DI). The patients was treated by aqueous pitressin and saline administration to control urinary output and keep positive salt balance at the same time. The other case with GH-producing macro-adenoma show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 8 publications
2
19
0
1
Order By: Relevance
“…the coexistence of DI and csWs (mixed syndrome) observed in our patients has also been described by yamaki et al 17 , who studied two patients postoperatively following surgery for pituitary tumor and observed the presence of severe natriuresis and hyponatremia in a study patient who developed DI (fluid loss >2.36 ml/kg/h), which led the authors to conclude that hyponatremia resulting from csWs in intracranial diseases may develop in patients with DI. similar findings were described by laredo et al 29 , who reported hypernatremia resulting from DI, followed by hyponatremia due to sodium urinary loss compatible with csWs, in the immediate postoperative period of two neurosurgical patients.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…the coexistence of DI and csWs (mixed syndrome) observed in our patients has also been described by yamaki et al 17 , who studied two patients postoperatively following surgery for pituitary tumor and observed the presence of severe natriuresis and hyponatremia in a study patient who developed DI (fluid loss >2.36 ml/kg/h), which led the authors to conclude that hyponatremia resulting from csWs in intracranial diseases may develop in patients with DI. similar findings were described by laredo et al 29 , who reported hypernatremia resulting from DI, followed by hyponatremia due to sodium urinary loss compatible with csWs, in the immediate postoperative period of two neurosurgical patients.…”
Section: Discussionsupporting
confidence: 87%
“…Initially, hyponatremia in patients with intracranial disease was attributed to cerebral salt wasting syndrome (csWs), as proposed by Peters et al in 1950 13 . later, the syndrome of inappropriate antidiuretic hormone secretion (sIADH), described by schwartz et al in 1957 14 , became accepted as the principal cause of hypona-tremia in neurological patients with excessive urinary sodium loss, and the original concept of csWs was abandoned 1,8,[14][15][16][17] . Hypernatremia is the sodium disturbance least frequently found in these patients and its principal cause is neurogenic diabetes insipidus.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Reports of CSWS have appeared intermittently with 1 or several cases with predominantly intracranial diseases that presented with hyponatremia, concentrated urines, and high urinary sodium concentrations [34, 35, 36, 37, 38, 39, 40]. Some justify the designation of salt wasting by various means, including clinical evidence of dehydration, postural hypotension that is responsive to saline, inappropriately low plasma ADH levels, and measurements of CVP, red cell volume, plasma volume (by radiolabelled serum albumin), and chloride or bromide spaces.…”
Section: Cerebral Salt Wastingmentioning
confidence: 99%